2020
DOI: 10.1002/admi.201902132
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Growth of Germanene and Stanene Lateral Heterostructures

Abstract: of a band gap in its electronic structure is difficult, these novel 2D materials are expected to possess sizeable band gaps, making them typically suitable for electronic applications. Furthermore, theory predicts that they are robust topological insulators, even up to about room temperature (RT) and above for germanene and stanene.In experiment, these artificial 2D materials were firstly realized in situ by molecular beam epitaxy (MBE) for silicene in 2012, [1,2] germanene in 2014, [3] stanene in 2015, [4] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…(d) STM image of germanene/stanene LHSs. Reproduced with permission from ref . Copyright 2020 Wiley-VCH.…”
Section: Bottom-up Routes For Heterostructure Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…(d) STM image of germanene/stanene LHSs. Reproduced with permission from ref . Copyright 2020 Wiley-VCH.…”
Section: Bottom-up Routes For Heterostructure Growthmentioning
confidence: 99%
“…With these merits, HS direct growth under UHV conditions is a marvelous choice for some in situ or quasi- in situ characterizations, such as STM characterization. Ogikubo et al designed a preparation solution by comprehensively using both atomic segregation epitaxy and MBE under UHV conditions to form stanene/germanene LHSs (Figure d) . The growth procedure under ultrahigh vacuum conditions is at variance with both solution synthesis and CVD/PVD methods due to the UHV condition without other gas flow and solution atmospheres.…”
Section: Bottom-up Routes For Heterostructure Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] Germanane exhibits many interesting and appealing properties including a direct bandgap of 1.59 eV, [100] high carrier mobility of >10 4 cm 2 V −1 s −1 , [101] high thermal stability of up to 75 °C in ambient conditions, [45] low effective mass, [102] and the operation of both electron and hole transport regimes with an on/off current ratio of up to 10 5 (10 4 ). [103] While both Ge [104][105][106] and GeH [107,108] have been widely synthesized via the epitaxial growth method, a limited number of studies on their exfoliation by liquid-phase protocols have been reported. To the best of our knowledge, Goldberger and his colleagues were the first to report the preparation of a hydrogenterminated germanium via the topochemical deintercalation of CaGe 2 .…”
Section: Germananementioning
confidence: 99%
“…Although germanene has not been found in nature, it can be synthesized by a few methods, such as molecular beam epitaxial (MBE) [16] and topological deintercalation [17].…”
Section: Introductionmentioning
confidence: 99%